Are there any effects of chronic carbon monoxide exposure on argyrophilic nucleolar-organizing region–associated protein synthesis in rat myocardium?. (September 2016) - Saritas, A; Gunes, H; Colakoglu, S; Eroz, R; Akoz, A; Oktay, M; Buyukkaya, A; Kandis, H; Ozkan, A
The aims of the study are to detect whether there are any possible effects of chronic carbon monoxide (CO) exposure on the argyrophilic nucleolar-organizing region (AgNOR)–associated protein synthesis and evaluate any possible relationship between the amount of AgNOR protein and the level of myocardial injury also and between AgNOR and histopathological evaluation methods. Adult male albino Wistar rats ( n = 18) were randomly divided into three groups (groups A, B, and C). Group A served as control, while groups B and C were rats exposed to CO gas chronically (1000 and 3000 ppm CO concentration with a flow rate of 4 L/min for 30 min/day for 7 days, respectively). Total AgNOR area/nuclear area (TAA/NA) and the mean AgNOR numbers for each myocyte nucleus were determined. There were significant differences among all groups for TAA/NA ratio. These differences were not significant for mean AgNOR numbers. According to the histopathological evaluation scores, there were significant differences between the groups. The differences were significant among the groups for loss of sarcomere pattern. A strong positive correlation between histopathological injury scores and TAA/NA ratio was found ( R sq = 0.48; p = 0.002), however, the correlation was not significant for mean AgNOR numbers ( R sq = 0.08; p = 0.25). In conclusion, TAA/NA ratio can be used as an indicator for obtaining information about the level of myocardial damage instead of histopathological evaluation scores.